Anesthesia of Nilem Fish (Osteochilus hasselti) With The Use of Clove Oil (Eugenia aromatica) in Different Dosages - Taufik Budhi Pramono; Marhaendro Santoso; Hana Roudhotul Jannah (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2022)
The natural ingredient of clove oil can be used for fish anesthesia because it contains eugenol metabolite compounds. The study aims was to determine the effect of clove oil in induction and recovery time, survival and optimum dose for the anesthesia process of Nilem fish. The randomized trial design was complete with four treatments and four tests. Treatment dose 0.05; 0,10; 0,15; 0.20 mL/L is applied. The fastest induction time process at the 0.20 mL/L treatment, while the recovery time at the 0.05 mL/L treatment and 100% survival at the 0.10 mL/L treatment.